Deteksi Posisi Plat Nomor Kendaraan Bermotor Pada Video Menggunakan Metode Frame Difference - Setiabudi, Muhamad Indra; Candra, Feri (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2021)
In this increasingly modern era, technological development have been spreading to various fields. One of those fields is computer vision on recognizing various object. There are several methods that usually used on object recognition. Frame difference is one of those methods that popularly used on object recognition. The frame difference method detect an object by calculating the pixel differential of two or more picture. Vehicle license plate is one of the popular objects that is studied in the field of computer science. It is because the license plate recognation can be implemented on various field such as parking system, tax system, traffic violations detector system and many more. In general, research on vehicle license plate recognition is done on static image and not moving image. Therefore, the author done this detection of vehicle license plate potition on a video research with the hope that it can become a reference for the readers and the world of research in detecting number plates. This research was tested using 10 videos of moving motorcycle. The result show that the system was able to recognize and capture 7 out of 10 license plate. From the result we can see that the system reaches 70% on accuracy.Keyword: Ocject Recognition, License Plate Detection, Frame Difference